10.1016/s1558-0164(11)70452-7 (CrossRef Listing of Deleted DOIs, 2000)
Evidence about the role of acute kidney injury (AKI) in idiosyncratic drug-induced liver injury (DILI) is still scarce. We aimed to ascertain the incidence, clinical profile, culprit drugs, and prognosis associated with concomitant DILI and AKI. We include patients from two long-term prospective DILI registries, the Spanish DILI registry and the Latin American DILI (LATINDILI) Network. Demographics, clinical characteristics, and outcome of patients with DILI-AKI were compared to those patients with DILI and without AKI. Overall, 54 out of 978 patients had AKI at the time of DILI diagnosis (5.5%). The most frequent culprit drug implicated in DILI-AKI was amoxicillin-clavulanate (11%) followed by anabolic androgenic steroids, antituberculosis drugs, ebrotidine, and ticlopidine (5.5% each). DILI-AKI cases were older than patients without AKI (60 ± 18 vs. 52 ± 18; P = 0.001), and mostly men (63%; P = 0.022). Furthermore, DILI-AKI cases showed higher comorbidity burden, and cholestatic damage and lymphopenia were more prevalent. Notably, DILI-AKI cases had higher incidence of liver-related death and all-cause mortality than those patients with no renal dysfunction (P = 0.029 and P = 0.015, respectively). In both a multivariable logistic regression (odds ratio [OR] = 3.46; 95% confidence interval [CI] 1.39-8.59; P = 0.008), and a rigorous propensity score-matched analysis (OR = 5.20; 95% CI 1.06-25.52; P = 0.042), renal damage was found as a risk factor of poor outcome. In conclusion, AKI in DILI mostly occurs in older male patients with cholestatic injury, lymphopenia, and greater burden of comorbidities, but mortality is restricted to DILI-AKI patients with hepatocellular damage. Overall, AKI is a risk factor of poor outcome in idiosyncratic DILI.